Greenstone‐Up Shear Sense at the Margin of the Mt Edgar Dome, East Pilbara Terrane: Implications for Dome and Keel Formation in the Early Earth. Issue 4 (22nd April 2022) - Roberts, Nicolas M.; Tikoff, Basil; Salerno, Ross A.
Abstract: The Paleoarchean Mt Edgar dome in the East Pilbara Terrane has long been studied as an archetypal dome within Archean dome‐and‐keel terranes, but the history of its formation is debated. Kinematic data presented in this study provide new insights into the late‐stage development of the Mt Edgar dome and East Pilbara Terrane. Quartz crystallographic preferred orientation (CPO), optical microstructures, and field structures all indicate that the granite‐greenstone contact of the Mt Edgar dome experienced reverse (greenstone‐up, dome‐down) sense of shear after the formation of the dominant schistosity. This reverse sense of shear is observed at localities along the entire extent of the sheared margin that rings most of the Mt Edgar dome, but is best documented along the southwest margin in the Warrawoona Greenstone Belt. Additionally, quartz CPO data from a dome triple junction outside of the sheared margin dominantly indicate a constrictional strain geometry, consistent with the previous interpretation that this area represents a zone of vertical foundering in a buoyancy‐instability driven system. However, buoyancy‐instability models do not necessarily predict the occurrence of greenstone‐up sense of shear preserved in solid‐state fabrics along the dome margin. Several geologic explanations are considered, including dome expansion or post‐doming deformation. The data are most consistent with explanations that directly relate to dome formation, especially when considered in tandem with recently published structural data from within the Mt Edgar dome. These kinematic data suggest that late dome development occurred in a near‐static crustal environment rather than an extensional or contractional setting. Key Points: The granite‐greenstone interface at the margin of the granitic Mt Edgar dome is characterized by a late‐stage greenstone‐up sense of shear Strain geometry within the Warrawoona Greenstone Belt varies from constrictional to flattening The East Pilbara Terrane domes likely formed as diapiric structures in a near‐static crust